A produção de loteamentos urbanos em Santo Antônio de Jesus/Bahia e seus principais conflitos - Neri, Maria Fabiana Barreto (2022)
The present work has as general objective to analyze the main conflicts present in the production of subdivisions in the urban space of Santo Antônio de Jesus, during the period from 1990 to 2020. The conflicts analyzed were those produced and/or mediated through the action of land, real estate and public authorities in urban, environmental and land issues, linked to the production of these projects. In order to carry out the research, some methodological procedures were used, such as: literature review on the production of urban space and subdivisions; documental research in bodies such as SEINFRA, INCRA, Public Ministry, 1st and 2nd Real Estate Registry Offices and EMBASA, which enabled the collection of data and information, as well as the delimitation of subdivisions built in the period under study; and conducting interviews with SEDEMA and some land developers. Therefore, it was found that the implementation of this type of enterprise has occurred, at least, since the 1970s and contributed to the process of production and expansion of the (i)legal city. In Santo Antônio de Jesus there are subdivisions that, in a first analysis, would be considered legal, as they have approval from the municipality and registration in the Real Estate Office. However, in reality, they present irregularities, either because they were implemented in disagreement with what was approved, due to the non-implementation of all the infrastructure required in the regulations, subdivisions that were closed without proper legal authorization, projects that caused serious environmental problems in the implementation process, etc. There are also subdivisions not registered in the Land Registry Offices, despite the fact that, in some cases, they have the approval of the municipality. They generally have environmental, urban and land tenure problems. However, in addition to the developers who act in disagreement with the law, the State is also responsible for these problems when it does not punish this type of entrepreneur, by carrying out the monitoring and inspection of the processes of subdivision of the land in an insufficient way, by not ensuring to the population of lower purchasing power policies that enable quality housing in suitable locations. Therefore, it is essential to comply with the legislation in the construction of these projects, as this would guarantee the rights of the purchasers of the lots and could avoid or mitigate the aforementioned problems. However, it should be noted that the production of the city in accordance with legal regulations is not enough to resolve all socio-spatial conflicts, since, like the urbanization process, laws are produced within an unequal society, contradictory and focused on meeting the demands and interests related to the reproduction of capital.